Accelerated exciton dissociation and electron extraction across the metallic sulfide–carbon nitride ohmic interface for efficient photocatalytic hydrogen production. Issue 30 (22nd July 2021) - Zhou, Jun; Zhang, Junjie; Zhao, Jing; Wang, Haozhi; Liu, Rui
Abstract : The metallic sulfide–CN ohmic junction has been rationally designed and prepared for modulating charge separation in a semiconductor photocatalyst. Abstract : Herein, a MOF derived transition metal sulfide (Co3 S4 ) with a metallic characteristic is introduced to create an ohmic contacted Co3 S4 –CN heterojunction interface. By virtue of electron injection from the lower work function Co3 S4 to the g-CN semiconductor, an intensive interfacial electric field is produced and causes downward band bending of g-CN. This Co3 S4 –CN heterojunction not only accelerates the exciton dissociation, but also eliminates the potential barrier for majority carrier (electron) extraction from g-CN, which synergistically promotes the charge separation. The Co3 S4 mediated performance enhancement in hydrogen production is proven to be comparable with that of noble metal Pt, and the as-obtained CNCo-3 exhibits superior photocatalytic activity in visible light driven hydrogen evolution (∼217.0 μmol g −1 h −1 ). The findings uncover the fundamental mechanism of metallic sulfide mediated charge separation and pave the way for regulating interface charge separation in photocatalysis through the use of other metallic sulfides ( e.g. Ni2 S).